Big Brave Brian - Robertson, M. P. (Frances Lincoln Children's Books, 2007)
Big Brave Brian is the bravest man in the world. His house is filled with hideous beasts: disgusting, slimy bog monsters, fearsome giants, and all manner of mysterious things that go bump in the night. But there is one thing that Brian is terrified of, and it' s in his bedroom, waiting for him to come in . . . Brian' s collection of wonderfully grotesque creatures appeals to children's sense of fun, and his amusing, surprising fear of cleaning his room provides the perfect starting point to discuss a young child' s own fears and worries.